Isolation, identification and characterization of a novel high level β-glucosidase-producing Lichtheimia ramosa strain - Gonçalves, Fabiano Avelino; Leite, Rodrigo Simões Ribeiro; Rodrigues, André [UNESP]; Argandoña, Eliana Janet Sanjinez; Fonseca, Gustavo Graciano (Elsevier, 2013)
The aim of this work was to prospect for microorganisms in the local environment, selecting those with higher production of cellulolytic and hemicellulolytic enzymes. A total of 36 microorganisms were isolated in a sugarcane-based medium. Colonies were replated in medium containing carboxymethylcellulose as the main carbon source, where all grew, confirming their potential for plant biomass degradation. The enzyme production was evaluated by cultivating the isolated microorganisms in solid-state bioprocess using two different carbon sources, sugarcane bagasse and wheat bran. Among the microorganisms obtained, isolate 11, identified as Lichtheimia ramosa, presented a high level β-glucosidase production of 15.58. U/mL, as well as 2.41. U/mL of xylanase and 2.13. U/mL of CMCase when cultivated on wheat bran. Changes in temperature and cultivation time favored a higher production of β-glucosidase: 17.26. U/mL in wheat bran-based medium at 35. °C for 120. h. © 2013 Elsevier Ltd.
Keywords: Screening; Sugarcane bagasse; Wheat bran